Associations Between Cohabitation, Marriage, and Suspected Crime: a Longitudinal Within-Individual Study - Airaksinen, Jaakko (Journal of developmental and life-course criminology, 2023)
The effects of marriage on criminal behavior have been studied extensively. As marriages today are typically preceded by cohabiting relationships, there is a growing need to clarify how different relationship types are associated with criminality, and how these effects may be modified by relationship duration, partner’s criminality, and crime type. We used Finnish longitudinal register data and between- and within-individual analyses to examine how cohabitation and marriage were associated with suspected crime. The data included 638,118 residents of Finland aged 0–14 in 2000 and followed for 17 years for a suspected crime: having been suspected of violent, drug, or any crime. Between-individual analyses suggested that those who were cohabiting or married had a 40–65% lower risk of being suspected of a crime compared to those who were single, depending on the type of crime. The within-individual analysis showed a 25–50% lower risk for suspected crime when people were cohabiting or married compared to time periods when they were single. Those in a relationship with a criminal partner had 11 times higher risk for suspected crime than those in a relationship with a non-criminal partner. Forming a cohabiting relationship with a non-criminal partner was associated with reduced criminality. The risk reduction was not fully explained by selection effects due to between-individual differences. Marriage did not introduce further reduction to criminality. Our findings demonstrate that selection effects partly explain the association between relationship status and criminality but are also compatible with a causal effect of cohabitation on reduced risk of being suspected of a crime.